THE INFLUENCE OF WORK CULTURE AND PROFESSIONAL DEVELOPMENT ON TEACHER QUALITY AND ITS IMPACT ON LEARNING QUALITY AT PUBLIC ELEMENTARY SCHOOLS IN SAKETI DISTRICT, PANDEGLANG REGENCY - Nurhasanah, Eneng; Rustandi, Tata; Permana, Angrian (Yayasan Education and Social Center, 2025)
This research was conducted at public elementary schools in Saketi District, Pandeglang Regency. The background of this study lies in the issues related to work culture, professional development, teacher quality, and learning quality. The purpose of this study is to analyze the influence of work culture and professional development on teacher quality, as well as the effect of teacher quality on learning quality. In addition, this study aims to determine whether teacher quality mediates the relationship between work culture and learning quality. The method used is quantitative, with a population of 259 and a sample size of 90. The analytical tool applied is regression analysis using Smart PLS software. The results of this research indicate that organizational culture and professional development have a positive and significant effect on teacher quality, and teacher quality has a positive and significant effect on learning quality. Furthermore, the findings reveal that teacher quality mediates the relationship between work culture and professional development on learning quality. It can be concluded that better work culture and professional development will improve teacher quality and, in turn, enhance learning quality. When teacher quality increases, work culture and professional development will contribute to improving learning quality.